2020
DOI: 10.1002/ejic.202001003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Heterogenized Cp*Ir Water Oxidation Catalysts Bearing Glyphosate and Glyphosine as Ancillary and Anchoring Ligands

Abstract: Two hybrid materials (1_TiO 2 and 2_TiO 2) were designed and prepared by anchoring novel [Cp*Ir(k 3-O,N,O-glyphosate)] (1; glyphosate = N-(phosphonomethyl)glycine) and [Cp*Ir(k 3-O,N,Oglyphosine)] (2; glyphosine = N,N-bis(phosphonomethyl)glycine) complexes onto rutile TiO 2. Characterization in solution (NMR spectroscopy) and solid state (X-Ray diffractometry) indicates that 1 and 2 are stabilized by the two arms of the glycine fragment, whereas they have (2) or can easily generate (1 and 2) a dandling phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Despite the use of homogeneous catalysts has historically pioneered the field of WO, pointing to an optimization of the recyclability of noble metals, the exploitation of immobilized catalysts turned out to be a successful strategy, too. [7,11,[15][16][17][18][19] Many molecular catalysts have been immobilized onto various supports such as semiconducting titanium oxide (TiO 2 ), [14,18,19,23,24] indium tin oxide (ITO), [25] bismuth vanadate (BiVO 4 ) [21,26,27] or inert porous supports like MOFs [28][29][30] or silica (SiO 2 ). [31,32] For instance, in a recent research, Inagaki reported the use of periodic mesoporous organosilica (PMO) with embedded bipyridine ligands (BPy-PMO) as support for the synthesis of a single site IrÀ Cp* WOC (Ir-BPy-PMOs).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of homogeneous catalysts has historically pioneered the field of WO, pointing to an optimization of the recyclability of noble metals, the exploitation of immobilized catalysts turned out to be a successful strategy, too. [7,11,[15][16][17][18][19] Many molecular catalysts have been immobilized onto various supports such as semiconducting titanium oxide (TiO 2 ), [14,18,19,23,24] indium tin oxide (ITO), [25] bismuth vanadate (BiVO 4 ) [21,26,27] or inert porous supports like MOFs [28][29][30] or silica (SiO 2 ). [31,32] For instance, in a recent research, Inagaki reported the use of periodic mesoporous organosilica (PMO) with embedded bipyridine ligands (BPy-PMO) as support for the synthesis of a single site IrÀ Cp* WOC (Ir-BPy-PMOs).…”
Section: Introductionmentioning
confidence: 99%
“…The retained piano-stool geometry of the complexes was supported by XRD. The hybrid materials that were derived from supporting the above complexes onto rutile TiO 2 were found to be effective molecular catalysts in water oxidation [ 31 ]. In another study, aminophosphonate complexes of [(η 6 - p -cym)Ru] 2+ were used as catalysts to reduce ketones, however, in this case, the phosphonate units were not in the coordination sphere of metal ion [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalytic water splitting to produce hydrogen directly by solar energy has been regarded as an affordable and sustainable manner to alleviate the two challenges at once. [1][2][3] However, the overall efficiency of water photosplitting is greatly restricted by the sluggish kinetics of H 2 O oxidation half-reaction for O 2 evolution, [4][5][6][7] as it necessitates the transport of four electrons and protons, and the formation of two OÀ O bonds, simultaneously. Therefore, developing efficient and stable water oxidation photocatalysts workable under visible light is highly desirable, toward the production of "green" hydrogen via H 2 O splitting, especially those made from lowcost elements.…”
Section: Introductionmentioning
confidence: 99%